Sistem Penyimpanan Arsip Pada Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Barat - Novadilastri, Novadilastri; Afifah, Afifah; Sari, Maya Permata; Sani , Neshy Aulia (CV. ITTC INDONESIA, 2023)
An archive storage system is a system used for document storage to make it easier to store and quickly find documents that have been stored if needed at any time. Proper storage of government archives is very necessary to maintain and preserve documents so they can be used and found again in the future. Some of the obstacles faced by the Administration and Personnel Subdivision of the West Sumatra Province Regional People's Representative Council Secretariat in managing incoming and outgoing letters is that it takes quite a long time to search for certain letters. The research method used is data collection through observation . Archives at the Secretariat of the Regional People's Representative Council of West Sumatra Province are stored in a filing cabinet, this functions to save archive storage space.